ANALISIS PERBANDINGAN HARGA SAHAM PT BANK CENTRAL ASIA Tbk. SEBELUM DAN SESUDAH STOCK SPLIT - Tiara Widya Antikasari (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Abstract Companies that have good performance will have stock prices that tend to be high. this will make it difficult for investors with small capital to invest. the company can take corporate action in the form of a stock split. The purpose of this study is to see the difference in stock prices before and after the stock split. using stock closing price data 14 days after and 14 days before the stock split conducted by PT. Bank Central Asia on October 13, 2021. This study uses a different test analysis using the Paired Sample T-Test to find out whether there is a significant difference in the price of shares before and after the stock split Test results of the Paired Sample T-Test before and after the stock split of stock prices prove a drastic difference. Keywords: stock, stock split, stock price